The power of working longer. (1st March 2019) - Bronshtein, Gila; Scott, Jason; Shoven, John B.; Slavov, Sita Nataraj
Abstract: This paper compares the relative strengths of working longer vs. saving more in terms of increasing a household's affordable, sustainable standard of living in retirement. Both stylized households and actual households from the Health and Retirement Study are examined. We assume that workers commence Social Security benefits when they retire. The basic result is that delaying retirement by 3–6 months has the same impact on the retirement standard of living as saving an additional one-percentage point of labor earnings for 30 years. The relative power of saving more is even lower if the decision to increase saving is made later in the work life. For instance, increasing retirement saving by one percentage point 10 years before retirement has the same impact on the sustainable retirement standard of living as working between 1 and 2 months longer. The calculations of the relative power of working longer and saving more are done for a wide range of realized rates of returns on saving, for households with different income levels, and for singles as well as married couples. The results are quite invariant to these circumstances.